Growth and Characterization of Ge100-xDyx(x≤2) Nanowires - K. B. Paul; G. I. Athanasopoulos; C. C. Doumanidis; C. Rebholz (Advances in Condensed Matter Physics)
Novel semiconducting Germanium-Dysprosium nanowires are fabricated by a combined two-step method, which consists of initial arc-melting of the elemental constituents into a pellet and its heat treatment, followed by thermal vapor transport of the powdered pellet in a tube reactor for fabrication of the nanowires. The nanomaterials are fabricated on gold nucleation seeds on Si/SiO2 substrates. The thermodynamic conditions in the reactor are carefully chosen to produce wires with diameters in a narrow, specific range. This nanofabrication method ensures high phase purity and crystallinity of nanowires. Based on the results and theoretical work, it is concluded that the fabricated Ge98Dy2 materials are in a glassy state below 20 K.